Testing for Environmental Kuznets Curve: A Case of Three Indicators of Environmental Quality in Nepal (Economic Journal of Nepal, 2014)
Testing for the Environmental Kuznets Curve (EKC) has been very popular in order to find out the possible self-correcting nature of the environmental pollution with the economic development. This paper tries to estimate an EKC relationship between the broad prosperity index and three measures of environmental qualities in the districts of Nepal. This attempt is different from other EKC studies on the ground that it uses the environmental qualities as the dependent variable instead of the environmental pollution, and the broad measure of prosperity index as the main explanatory variable. Despite the existence of the U-shaped relationship between the prosperity index and the measures of environmental qualities, the findings do not support the hypothesis that there exists a meaningful EKC relationship in the context of the three measures of environmental qualities, at least in the present analysis, in Nepal. It has a far-reaching policy implication that the environmental quality does not improve itself. Effective policy intervention is required to that end.The Economic Journal of Nepal, Vol. 34, No. 1, January - March 2011 (Issue N0. 133)Uploaded date: 3/27/2014